A New Flavonoidal Constituent from Taraxacum officinale (L.) Weber - Nath Yadava, Raj; Khan, Shirin (Asian Journal of Chemistry, 2013)
A new flavone glycoside (A) m.p. 265-268 ºC, m.f. C33H40O21, [M]+ 742 (FABMS), has been isolated from stem of Taraxacum oficinale (L.) Weber. It was characterized as 3,5,7,3',4'-pentahydroxy 8-C methyl flavone 7-O-b-D-xylopyranosyl (1®4)O-b-D glucopyranosyl 3'-O-a-L-rhamnopyranoside alongwith known compound ladanein B by various chemical degradations and spectral analysis.